Construction of self-reinforced polymer based energetic composites with nano-energetic crystals to enhance mechanical properties. (November 2021) - Lin, Congmei; Huang, Bing; Yang, Zhijian; Gong, Feiyan; Zhao, Xu; Pan, Liping; Zhang, Jianhu; Liu, Shijun; Liu, Jiahui; Li, Jiang; Guo, Shaoyun
Abstract: Nano-fillers have attracted a large amount of attention in enhancing the mechanical properties of polymer bonded explosive (PBX), due to the strong interfacial interactions. However, the addition of inert components reduces the energy output and makes the processing, recycling and re-utilization of energetic composites quite unfavorable. To improve the mechanical properties while maintaining detonation performance, a novel self-reinforced PBX was constructed with very low content of nano-1, 3, 5-triamino-2, 4, 6-trinitrobenzene (TATB) served as modifiers. The incorporation of nano-TATB particles into PBX evidently increased the storage modulus, strength, and toughness. The enhanced mechanism could be ascribed to the nano effect of nanoparticles and "interlocking block" formed on the rough surface of nano-TATB, which provided stronger interfacial interaction. This work demonstrates the successful application of nano-energetic crystals to self-reinforce PBXs, thereby opening up new perspectives in structure design and modification of mechanical properties for energetic composites without changing the intrinsic components of energetic composites.